Interregional Interdependence among Ecuadorian Provinces: An Input-Output Analysis - Eduardo Haddad; Juan Manuel Samaniego; Alexandre Porsse; Santiago Ochoa; Luiz Gustavo Souza (European Regional Science Association (ERSA), 2011)
In this paper, we explore the structural characteristics of the interregional input-output system developed for Ecuador for the year 2007. As part of an ongoing project that aims to develop an interregional CGE model for the country, this database was developed under conditions of limited information. It provides the opportunity to better understand the spatial linkage structure associated with the national economy in the context of its 22 provinces, 15 sectors and 60 different products. This exploratory analysis is based on the description structural coefficients and the use of traditional input-output techniques. Finally, we further explore the spatial linkage structure by looking at the decomposition of final demand components. It is hoped that this exercise might result in a better appreciation of a broader set of dimensions that might improve our understanding of the integrated interregional economic system in Ecuador.
Keywords: 330